1987
DOI: 10.1073/pnas.84.9.2891
|View full text |Cite
|
Sign up to set email alerts
|

Loss of an apurinic/apyrimidinic site endonuclease increases the mutagenicity of N-methyl-N'-nitro-N-nitrosoguanidine to Escherichia coli.

Abstract: xthA-Escherichia coli, which are missing a major cellular apurinic/apyrimidinic (AP) endonuclease, are 5-to 10-fold more sensitive than xthA+ bacteria to mutagenesis by N-methyl-N'-nitro-N-nitrosoguanidine (MNNG) under conditions that induce the "adaptive response." The xthA--dependent mutations are also dependent on SOS mutagenic processing and consist of both transversion and transition base substitutions. When MNNG-adapted xthA-bacteria are challenged with a high dose of MNNG, more xthA-dependent SOS-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…AP sites AP sites in DNA arise spontaneously through depurination (Lindahl & Nyberg, 1972 Kunkel, 1984;Miller & Low, 1984;Gentil et al, 1984;Loeb, 1985;Granger-Schnarr, 1986;Cunningham et al, 1986;Loeb & Preston, 1986;Foster & Davis, 1987). Analysis of DNA synthesis on templates containing AP sites has shown that dAMP residues are preferentially introduced opposite these lesions (Boiteux & Laval, 1982;Strauss et al, 1982;Schaaper et al, 1983;Kunkel, 1984).…”
Section: Dna Lesions and Their Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…AP sites AP sites in DNA arise spontaneously through depurination (Lindahl & Nyberg, 1972 Kunkel, 1984;Miller & Low, 1984;Gentil et al, 1984;Loeb, 1985;Granger-Schnarr, 1986;Cunningham et al, 1986;Loeb & Preston, 1986;Foster & Davis, 1987). Analysis of DNA synthesis on templates containing AP sites has shown that dAMP residues are preferentially introduced opposite these lesions (Boiteux & Laval, 1982;Strauss et al, 1982;Schaaper et al, 1983;Kunkel, 1984).…”
Section: Dna Lesions and Their Repairmentioning
confidence: 99%
“…Church and Gilbert (1984) can be used in mutation studies. An alternative would be to amplify the region of interest (Saiki et al, 1985 (Lindahl, 1982;Cunningham et al, 1986;Smith, 1987;Foster & Davis, 1987;Yatagai et al, 1987). Some of the DNA-repair systems involved in the correction of alkylation damage and complex lesions are present in very small amounts intracellularly, but are inducible in E. coli (Witkin, 1976;Lindahl, 1982;Walker, 1984).…”
Section: Possible Future Directionsmentioning
confidence: 99%
“…True revertants of hisG428 were first identified by the transfer of the His + phenotype upon mating and then were sequenced (Foster and Davis, 1987). Suppressor tRNAs of hisG428 were identified by their ability to suppress known ochre mutations in the lacI gene, as has been described (Foster and Eisenstadt, 1985).…”
Section: Analysis Of Mutationsmentioning
confidence: 99%
“…All E. coli strains used in this study are derivatives of PF260 (= F − ara Δ (gpt-lac-pro) thiA Δhis5 supD60; Foster and Davis, 1987). Construction of DNA repair-deficient derivatives was as previously described for uvrB5 (Foster et al, 1983), ΔxthA and umuC122::Tn5 (Foster and Davis, 1987).…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation